The Transformation of Digital Technology-Based Maritime Transportation Systems in Enhancing Shipping Efficiency and Safety - Ihrof Muzarodin; Heru Maryanto; Antaris Fahrisani; Pierre Marcello Lopulalan (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of digital technology has transformed the marine transportation system and created a huge opportunity to improve shipping efficiency and safety. This research aims to analyze the transformation of maritime transportation systems based on digital technology in improving operational efficiency and shipping safety. The research uses a qualitative approach with a case study method through in-depth interviews with 15 informants consisting of ship operators, port managers, and maritime authorities. Data was analyzed using thematic analysis techniques through the process of data reduction, data presentation, and conclusion drawn. The results of the study show that the application of digital navigation systems, real-time monitoring, and integration of logistics data is able to increase operational effectiveness, accelerate information distribution, and minimize the risk of marine accidents. This study concludes that digital transformation plays an important role in supporting safer, more efficient, and sustainable maritime transportation systems.